'Only Tonga spoken here!': Family language management among the Tonga in Zimbabwe. Issue 4 (2nd October 2019) - Maseko, Busani; Mutasa, Davie E
Abstract: This article analyses language management strategies that are employed by Tonga parents towards the conservation of the Tonga language. Since Zimbabwe gained independence, Tonga, alongside a host of other previously designated minority languages has endured marginalisation in terms of use in public and official spaces, leading to language shift. In the presence of dominant endoglossic languages, Shona and Ndebele, within Tonga communities, Tonga speakers have found it difficult to maintain their language. In the context of family and societal bilingualism, parents, as the custodians of the home language are better placed to manage language use, for example, by encouraging and rewarding preferred language practices and sanctioning or punishing undesirable use. This study sought to understand some of the language management strategies that parents employ to promote the use of Tonga language at home. Deploying insights afforded by the language management approach, the reversing language shift theory and family language policy, the study reveals that Tonga parents have high impact beliefs regarding their potential to control their children's linguistic behaviour in the home. These impact beliefs tend to inform parental language management strategies.